Analisis Kendala Internal Mahasiswa dalam Menulis Karya Ilmiah - Rahmiati, Rahmiati (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2015)
This paper presents research on the analysis of internal constraints of students in writing scientific papers. The aim is to examine whether students about internal problems and solutions regarding their difficulties in writing academic work. The data generated from individual interviews and group discussions focused on 56 participants at the university. Data were analyzed using inductive and deductive approaches. The results showed some of the key findings related to internal barriers experienced by students in writing scientific papers. Among other issues relating to the nature lazy to write, lack of mood in writing, difficulties in finding topics or ideas for writing, lack of self-confidence to write and difficult to start writing. This article also reveals some internal strategic solutions to overcome the constraints of students, namely to build internal motivation to write, change paradigms related to writing, and efforts to be creative in writing.